Detection of Leishmania spp. in Bats from an Area of Brazil Endemic for Visceral Leishmaniasis. Issue 6 (24th February 2017) - de Rezende, M. B.; Herrera, H. M.; Carvalho, C. M. E.; Carvalho Anjos, E. A.; Ramos, C. A. N.; de Araújo, F. R.; Torres, J. M.; de Oliveira, C. E.
Summary: The multihost parasites Leishmania spp. infect a broad range of wild mammalian species including bats. Several species of bats have adapted to a variety of food resources and shelters in urban areas. This study aimed to detect Leishmania spp. DNA in bats present in forest fragments located in metropolitan areas endemic for leishmaniasis in Campo Grande, Mato Grosso do Sul (MS), Brazil. Blood samples were obtained from 80 individuals, including eight species of Phyllostomidae and one species of Vespertilionidae. Thirty of the 80 bats were positive for Leishmania spp. using conventional PCR, all belonging to the family Phyllostomidae. Eighteen samples tested by real‐time PCR (qPCR) using specific primers for the kDNA of Leishmania infantum were positive. To the best of our knowledge, this is the first report detecting Leishmania spp. in Platyrrhinus incarum in addition to being the first reported detection of L. infantum in the bat species Phyllostomus discolor, Platyrrhinus lineatus, Artibeus planirostris and Artibeus lituratus . Our results show that bats can host Leishmania spp. in areas endemic for leishmaniasis, which must be taken into account in disease control operations by public health authorities.